SPECTROGRAM STUDY OF BODO VOWELS - Boro, Jogen (International Journal of Research -GRANTHAALAYAH, 2015)
Bodo Language is phonetically rich language but it is not analysed systematically and scientifically still now. So each and every parts of language is to be studied with the help of modern equipments for find out the accurate results. In the age of Information Technology where the Information Technology (IT) is threading the entire into a Global Village with knowledge as the prime currency and sole differentiator, development of appropriate access technology take part vital role for gaining the information. Especially for India, with its multi-lingual requirements and not so fortunate achievements in terms of overall literacy, development of speech technology in each of its recognized language demands utmost attention. Moreover, development of such Speech Technologies in Indian Languages, with their core dependence on linguistic and cultural ethos, need to be developed largely in India. From the present analysis and study of Bodo vowels spectrograms, it is seen that the lower frequency regions for almost all vowels are very clear. It is a very uncommon characteristic observed in case of the Bodo vowel utterances in comparison with other local languages of Assam. So this will help the speech researcher’s on Bodo Language in various directions in future.